Trichosporon isolation from human ungueal infections: is there a pathogenic role? - Alba Regina de Magalhães; Marília Martins Nishikawa; Silvia Suzana Bona de Mondino; Heloisa Werneck de Macedo; Elisabeth Martins da Silva da Rocha; Andrea Regina de Souza Baptista (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Although dermatophytes are considered the major cause of onychomycosis, many reports have incriminated non-dermatophyte moulds and yeasts in the disease's etiology. Successive Trichosporon isolation from onychomycosis has led to the genus being suspected as a nail primary pathogen. OBJECTIVE: To determine the prevalence of Trichosporon isolation in onychomycosis patients who attended a mycology diagnostic service in Rio de Janeiro, Brazil, between January 2003 and December 2006. The study also includes a worldwide review on Trichosporon isolation prevalence in ungueal disease, emphasizing T. ovoides. METHODS: This retrospective study was conducted with the support of staff from the Mycology Laboratory at the Dermatological Service of Rio de Janeiro's Santa Casa da Misericórdia (MLDS). RESULTS: Mycological analysis provided positive results equaling 47/5036 (0.93%) for Trichosporon spp.; obtained mainly as a single agent (72.35%), and from mixed cultures (27.65%; X2= 6.397; p= 0.018). The great majority belongs to the T. ovoides species (91.5%; n=43), obtained as a single isolate (74.41%; n= 32/43; X2 = 7.023; p= 0.014). CONCLUSIONS: Although T. ovoides is classically associated as an etiologic agent of white piedra, this study highlights its potential as a human nail disease pathogen. Our study opens doors for future epidemiologic and virulence factors aimed at determining whether T. ovoides is an important causative agent of onychomycosis in Brazil.